Peran Negara dalam Melindungi Hak-Hak Konstitusional Anak Terlantar di Indonesia - Faiz Asmi Permana; Septi Nur Wijayanti (Faculty of Law Universitas Muhamadiyah Yogyakarta, 2022)
Abandoned children are children whose parents for some reason neglect and or are unable to carry out their obligations so that their physical, spiritual and social needs are not met. This study aims to identify and examine the function and role of the state in implementing and protecting the constitutional rights of neglected children in Indonesia. This type of research is a normative research with a statutory approach. The data collection technique is through literature review, and analyzed using qualitative descriptive methods. The results of the study indicate that the function and role of the state in protecting the constitutional rights of neglected children is sufficient in accordance with the 1945 Constitution of the Republic of Indonesia Article 34 paragraph (1) where the State through the Ministry of Social Affairs provides programs related to facilities and infrastructure related to neglected children in order to get their rights, namely Through the Child Social Welfare Program (PKSA) in these programs many benefits are felt by the abandoned children such as getting a place to live, education, access to health, cash assistance, clothing, housing, and food. However, in the process of implementing child protection, there are too many legal rules that regulate so that it gives rise to multiple interpretations related to these legal rules, especially to the general public. Regarding the fulfillment of children's rights, there is a need for supervision regarding the Welfare Program provided by the Government to neglected children so that the provision of assistance is carried out evenly and on target.